2019
DOI: 10.5539/jas.v11n4p183
|View full text |Cite
|
Sign up to set email alerts
|

Sanitary and Physiological Quality of Soybean Seeds Treated With Ozone

Abstract: Widely used, the seeds chemical treatment can cause physiological quality loss due to phytotoxicity that the active principles may cause. In this context, the ozone gas stands out (O3) as efficient agent biocide, however its use in the pathogens control and their effects on the seeds physiological quality are still little studied. In this context, the objective was to evaluate the ozone gas efficiency as a controller agent of plant pathogens and its effect on the physiological quality of soybean seeds. For thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Nevertheless, a short time exposure was most beneficial. Similarly, Sudhakar et al [61], Abeli et al [70], Avdeeva et al [71], and Rodrigues et al [72] elucidated the positive impacts of low concentrations of O 3 on the germination and seedling parameters of tomato, alpine, wheat, and soybean, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…Nevertheless, a short time exposure was most beneficial. Similarly, Sudhakar et al [61], Abeli et al [70], Avdeeva et al [71], and Rodrigues et al [72] elucidated the positive impacts of low concentrations of O 3 on the germination and seedling parameters of tomato, alpine, wheat, and soybean, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…After 10 weeks of growth, the shoot and root biomass, root length, and stem diameter of the plants treated with 2.66 and 3.96 mg L -1 significantly increased. Rodrigues et al (2019) found that ozone exposure at a concentration of 25 g m -3 for 120 minutes had no effect on the physiological or biochemical processes of cultivar soybean seeds. According to Mohammad et al (2019), ozonizing at 5 mg L -1 for 20 minutes had no negative effects on the size, color, or germination percentage of alfalfa sprouts.…”
Section: Introductionmentioning
confidence: 90%
“…Peanut seeds increased ethylene production during after-ripening to relief dormancy [34]. Dormancy loss during after-ripening in sunflower seeds was correlated with a reduction in sensitivity to abscisic acid (ABA), an inhibitor of germination [35]. During after-ripening, wheat seeds became sensitive to treatment with gibberellin (GA), which promoted germination, and then became insensitive to ABA [15].…”
Section: The Effect Of Storage Time On Barley Germinationmentioning
confidence: 99%